Opportunity Analysis of Gelora Village as a Creative-Economy-Based Supporting Tourism Destination - Gufranuddin; Samsudin; Mira Sari; Doni Saihul Umam (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
This study analyzes the potential of Gelora Village to develop as a supporting tourism destination through the strengthening of its bamboo weaving creative economy. Although Gelora Village has not yet been formally designated as a tourism village, it possesses cultural and economic characteristics that position it strategically within the eastern Lombok tourism corridor. The research adopted a qualitative descriptive approach to examine internal and external factors affecting tourism-based economic development, supported by field observations, in-depth interviews, and documentation. SWOT analysis was applied to identify existing opportunities and limitations. Findings reveal that hereditary weaving skills and product diversity generate competitive strength for Gelora, especially due to proximity to the well-established Loyok Tourism Village. Community interest particularly from MSMEs and youth groups demonstrates social capital that can accelerate the development of tourism activities based on creative industries. However, barriers remain, including unstable production due to the prioritization of agricultural work, limited marketing channels, the absence of a showroom along tourist routes, and weak digital branding. Opportunities include cross-village tourism integration, experience-based tourism such as bamboo weaving workshops, and the establishment of an MSME gallery as a stopover point for visitors. Nevertheless, threats such as competition from more advanced bamboo craft centers, fluctuating artisan engagement, inconsistent government facilitation, and the risk of stagnation must be anticipated. Overall, the study concludes that Gelora Village has high potential to become a supporting tourism destination, provided professional management, market-oriented strategies, and sustainable collaboration are implemented.